2014
DOI: 10.1155/2014/572425
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Signs and Symptoms of Heart Attack and Stroke among Singapore Residents

Abstract: Aim. To determine the level of knowledge of signs and symptoms of heart attack and stroke in Singapore resident population, in comparison to the global community. Methods. A population based, random sample of 7,840 household addresses was selected from a validated national sampling frame. Each participant was asked eight questions on signs and symptoms of heart attack and 10 questions on stroke. Results. The response rate was 65.2% with 4,192 respondents. The level of knowledge for preselected, common signs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 18 publications
6
23
0
1
Order By: Relevance
“…In addition, the most common symptom recognised by the respondents was numbness or weakness of the face, arm or leg, followed by the immediate change in gait, sudden confusion, and difficulty in speaking. The results are in accordance with the studies in Nigeria, Singapore and China [27,[30][31][32].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In addition, the most common symptom recognised by the respondents was numbness or weakness of the face, arm or leg, followed by the immediate change in gait, sudden confusion, and difficulty in speaking. The results are in accordance with the studies in Nigeria, Singapore and China [27,[30][31][32].…”
Section: Discussionsupporting
confidence: 91%
“…Sudden numbness or weakness of the face, arm or leg was the most commonly recognized stroke symptom in this study. This is in agreement with studies in Spain, the US, and Singapore where the most frequent stroke symptom recognised was numbness or weakness of the face, arm or leg [27][28][29]. On the contrary, an Australian study reported paralysis or partial weakness as the lowest recognised symptom of stroke [25].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Few studies have assessed lay knowledge of the pain patterns for common clinical scenarios other than myocardial infarction. 12,13 It was notable that most participants (79.6 per cent) could accurately identify the typical location of pain associated with myocardial infarction, despite a significant number of participants incorrectly locating the heart (48.8 per cent). It is possible that this is a reflection of public health awareness campaigns on the symptoms of a heart attack.…”
Section: Researchmentioning
confidence: 99%